Response growth and production of maize (Zea mays L.) in the provision of biological fertilizer with different spacing of lowland - Wahyudi, Ilham; Hawalid, Heniyati; Hawayanti, Erni (Klorofil: Jurnal Penelitian Ilmu-Ilmu Pertanian, 2016)
Response growth and production of maize (Zea mays L.) in the provision of biofertilizer with differentspacing of lowland. This study aims to determine the effect of biological fertilizer with several different plant spacingon growth and production of maize in lowland. This research has been carried on in the land Campus C Faculty ofagriculture, University of Muhammadiyah Palembang, Hamlet 1 Semambu Island Village, North IndralayaSubdistrict, Ogan Ilir South Sumatra. This study was implemented from January s / d April 2015 This study used arandomized design Divided (Split Plot Design) and each treatment was rpeated 3 times. As the main plot treatmentwas planting distance, consisting of : (J1): Spacing 100x30 cm, (J2): Spacing 70x30 cm, (J3): Spacing 40x30 cm.Treatment subplot consisted of various types of fertilizers, comprising: (H0): Inorganic Fertilizers, (H1): BiofertilizersBio P, (H2): Azospirilium, (H3): Biofertilizer Bio P + Azospirilium. As well as all units in the given treatments ofchicken manure 4 ton ha-1. The results showed that the treatment plant spacing 100x30 cm give the highestinfluence on the growth and production of maize in lowland and tabulation fertilizer Bio P and Azospiriliumcombination provides the highest influence on the growth and production of maize in loeland. As well as theinteraction spacing of 100x30 cm and Bio P + Azospirilium combination gives the best effect on the growth andproduction of maize.